2015
DOI: 10.4028/www.scientific.net/amr.1134.75
|View full text |Cite
|
Sign up to set email alerts
|

Rubber-Solvent Interaction Parameter (χ<sub>1</sub><sub>,2</sub>) of NR/SBR Rubber Blend Solution in Determination of Crosslink Concentration for Vulcanized Rubber Blend

Abstract: Crosslink concentration is an important property affecting the major characteristic of cured rubber. One of the important parameter to determine the crosslink concentration of a vulcanized rubber by swelling measurement is the rubber-solvent interaction parameter known as ‘kai’ value denoted as χ. For single rubber, the χ value is known however, the χ1,2 for rubber blends are unknown. This research concerned with the investigation to determine the χ1,2 for rubber blends solution (uncured rubber). Natural rubbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Several studies have reported that increasing cross‐link density for an irradiated polymer can enhance its mechanical strength. [ 37,46,47 ] The increase in cross‐link density was concurrent with the enhancement in σ s and E in the NRL/SIS blend after exposure to 12 kGy irradiation. Figure 4C shows that at the highest irradiation dose of 16 kGy, the gel contents and cross‐link density decrease to 36.89% and 9.44 × 10 −5 mol cm −3 , respectively, which might be ascribed to the chain scission obtained from excessive absorbed energy.…”
Section: Resultsmentioning
confidence: 95%
“…Several studies have reported that increasing cross‐link density for an irradiated polymer can enhance its mechanical strength. [ 37,46,47 ] The increase in cross‐link density was concurrent with the enhancement in σ s and E in the NRL/SIS blend after exposure to 12 kGy irradiation. Figure 4C shows that at the highest irradiation dose of 16 kGy, the gel contents and cross‐link density decrease to 36.89% and 9.44 × 10 −5 mol cm −3 , respectively, which might be ascribed to the chain scission obtained from excessive absorbed energy.…”
Section: Resultsmentioning
confidence: 95%
“…where ν is the cross-link density mole per unit of volume (mol/ cm 3 ) and χ is the Flory-Huggins polymer-solvent interaction parameter (0.35 for the rubber-toluene mixture; (Dzulkifli et al, 2016).…”
Section: Cross-link Density Determinationmentioning
confidence: 99%
“…where ν is the cross-link density mole per unit of volume (mol/cm 3 ) and χ is the Flory-Huggins polymersolvent interaction parameter (0.35 for the rubber-toluene mixture; [27].…”
Section: Cross-link Density Determinationmentioning
confidence: 99%